Association and shared biological bases between birth weight and cortical structure - Lu Zhang; Qiaoyue Ge; Zeyuan Sun; Rui Zhang; Xinxi Li; Xiaoli Luo; Run Tian; Yuheng Cao; Chunyan Pu; Lin Li; Dongsheng Wu; Ping Jiang; et al. (Translational Psychiatry)
Abstract Associations between birth weight and cortical structural phenotypes have been detected; however, the understanding is incomprehensive, and the potential biological bases are not well defined. Leveraging data from genome-wide association studies, we investigated the associations and the shared transcriptomic, proteomic and cellular bases of birth weight and 13 cortical structural phenotypes. Mendelian randomization analyses were performed to examine associations between birth weight and cortical structure. Downstream transcriptome-wide association study (TWAS), proteome-wide association study (PWAS) and summary-based Mendelian randomization (SMR) analyses were utilized to identify the shared cis-regulated gene expressions and proteins. Finally, cell-type expression-specific integration for complex traits (CELLECT) analyses were conducted to explore the enriched cell types. The Mendelian randomization analyses found positive associations between birth weight and global cortical folding index, intrinsic curvature index, local gyrification index, surface area and volume. Downstream transcriptomic-level TWAS and SMR identified three gene expressions both linked to birth weight and at least one cortical structural phenotype (CNNM2, RABGAP1 and CENPW). Parallel PWAS and SMR analyses at the proteomic level identified four proteins linked to both phenotypes (CNNM2, RAB7L1, RAB5B and PPA2), of which CNNM2 was replicated. CELLECT analyses revealed brain cell types enriched in birth weight, including pericytes, inhibitory GABAergic neurons and cerebrovascular cells. These findings support the importance of early life growth to cortical structure, and suggest underlying transcriptomic, proteomic and cellular bases. These results provide intriguing targets for further research into the mechanisms of cortical development.